2002
DOI: 10.1105/tpc.000745
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Arabidopsis PHO1 Gene Involved in Phosphate Loading to the Xylem

Abstract: The Arabidopsis mutant pho1 is deficient in the transfer of Pi from root epidermal and cortical cells to the xylem. The PHO1 gene was identified by a map-based cloning strategy. The N-terminal half of PHO1 is mainly hydrophilic, whereas the C-terminal half has six potential membrane-spanning domains. PHO1 shows no homology with any characterized solute transporter, including the family of H ؉ -Pi cotransporters identified in plants and fungi. PHO1 shows highest homology with the Rcm1 mammalian receptor for xen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
493
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(532 citation statements)
references
References 52 publications
18
493
1
2
Order By: Relevance
“…We focused on a subset of 11 genes that each contain highly significant SNP associations (FDR: q < 0.05) (Table S2). Among these candidate genes is PHOSPHATE 1 or PHO1 (At3g23430) shown previously to play a role in inorganic phosphate loading into the xylem and aspects of root development (20,21). Several other uncharacterized genes were also identified.…”
Section: Identification Of Candidate Genes Underlying Natural Variatimentioning
confidence: 99%
“…We focused on a subset of 11 genes that each contain highly significant SNP associations (FDR: q < 0.05) (Table S2). Among these candidate genes is PHOSPHATE 1 or PHO1 (At3g23430) shown previously to play a role in inorganic phosphate loading into the xylem and aspects of root development (20,21). Several other uncharacterized genes were also identified.…”
Section: Identification Of Candidate Genes Underlying Natural Variatimentioning
confidence: 99%
“…The PHO1 protein, primarily expressed in the root vascular cylinder, is known for mediating Pi efflux in loading Pi to root xylem in Arabidopsis (Hamburger et al, 2002;Stefanovic et al, 2011). In rice, it has been shown that OsPHO1;2 plays an important role in transferring Pi from roots to shoots (Secco et al, 2010).…”
Section: Ospt1 Functions In Pi Acquisition and Distribution And Pi-mementioning
confidence: 99%
“…One particular allometric root phenotype that captures the proportion of LRs along the PR length was used for GWASs, and two genes underlying this trait were identified (PHOSPHATE1 [PHO1] and ROOT SYSTEMS ARCHITECTURE1 [RSA1]; Rosas et al, 2013). PHO1 was previously characterized as a phosphate transporter (Poirier et al, 1991;Hamburger et al, 2002), whereas RSA1 was a novel gene identified in the study to be involved in regulating root allometry . Interestingly, these allometric phenotypes were conditional to specific environments, and RSA1 and PHO1 mediated these responses in the context of auxin, ABA, and nitrate signaling pathways .…”
Section: Using Natural Variation To Identify Regulators Of Root Growtmentioning
confidence: 99%